Recurrent Idiopathic Gingival Hyperplasia - Rajkarnikar, Junima; Shrestha, Bikash Veer; Kumar, Santhosh (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Increase in size of the gingiva is termed as gingival enlargement. Most common type of gingival enlargement is inflammatory, which his caused due to plaque accumulation and improper oral hygiene maintenance. Orthodontic therapy can often lead to failure to improve oral hygiene. This case describes a recurrent, progressive gingival enlargement of a 19 year old female orthodontic patient in which gingivectomy was performed and repeated, which subsequently failed. Hence modified Widman’s flap was performed with medical supplements. Periodic periodontal check up is required in orthodontic cases to control the gingival inflammation. Patient compliance is also very important in such cases. There should be proper co-operation between the Orthodontist and Periodontist for successful treatment of gingival hyperplasia. Patients with such conditions should be carefully monitored and checked to avoid the recurrence and avoid further progression into chronic periodontitis.